Strategic ideas for balancing national food security and doubling farmers income - Voleti, S. R.; Meera, Shaik N. (Indian Farming, 2018)
The Indian Institute of Rice Research can also support seed systems of various states by providing better options of quality seed production and distribution. Reduced cost of cultivation with resource use efficiency will bring down cost of cultivation. Labour saving technologies such as mechanization, direct-seeded rice etc are standardized by IIRR. Low cost precision farming practices in farmers’ fields and Optimal Mechanization with custom hiring models could be evolved in due course.Increased cropping Intensity and Farming system approach can help poor farmers to increase per acre income. The IIRR can also facilitate digital strategies to drive science led farming in both these states. Intense efforts to bring faster, cheaper access to knowledge and inputs could be tried on pilot basis for benefitting rice farmers. There is a scope to intensify research on value-addition like the case of millets value added products. About one-third of the increase in farmers’ income is easily attainable through better price realization, efficient post-harvest management, competitive value chains and adoption of allied activities.